2019
DOI: 10.2355/isijinternational.isijint-2019-130
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Embrittlement Susceptibility Evaluation of Tempered Martensitic Steels Showing Different Fracture Surface Morphologies

Abstract: The effects of the crosshead speed, hydrogen content and temperature on fracture strength and fracture surface morphology were investigated using a tempered martensitic steel containing 1.67 mass% of Si (H-Si) and one containing 0.21 mass% of Si (L-Si). When L-Si specimens were charged with a small amount of hydrogen, fracture surfaces showed a transition from quasi-cleavage (QC) to intergranular-like (IG-like) to intergranular (IG) at room temperature. In contrast, when H-Si specimens were charged with a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…This is because the steels with the tensile strength of 1 200 MPa or less are not susceptible for hydrogen (Figs. 10,11). The TS-H = 1 126 MPa of the base metal specimen for the TM steel with hydrogen charging and the TS-W = 1 450 MPa of the welded specimen for the TM steel showed the similar strength as those of the HS1 steel (Fig.…”
Section: Effect Of Hydrogen On Tensile Propertiesmentioning
confidence: 72%
See 2 more Smart Citations
“…This is because the steels with the tensile strength of 1 200 MPa or less are not susceptible for hydrogen (Figs. 10,11). The TS-H = 1 126 MPa of the base metal specimen for the TM steel with hydrogen charging and the TS-W = 1 450 MPa of the welded specimen for the TM steel showed the similar strength as those of the HS1 steel (Fig.…”
Section: Effect Of Hydrogen On Tensile Propertiesmentioning
confidence: 72%
“…In the tempered martensitic steels with a tensile strength of 1 470 MPa grade with changing the additive amount of Si, occurring the quasi-cleavage and the intergranular fractures due to hydrogen, the effects of the strain rate, the hydrogen concentration and the temperature on the fracture strength and the fracture morphology of the round bar notched specimen have been investigated. 11) In addition, in the evaluation of the side collision of automobiles, the effect of the heat affected zone (HAZ) softening on the strength and the elongation of the spot-welded tensile specimens is considered since the flange of the B pillar on the side of the car body may occur the in-plate tensile deformation mode. 12) However, the sufficient research has not been conducted on the hydrogen embrittlement resistance of the spot-welded TM steels.…”
Section: Effect Of Hydrogen On Spot-welded Tensile Properties In Automotive Ultrahigh-strength Trip-aided Martensitic Steel Sheetmentioning
confidence: 99%
See 1 more Smart Citation
“…Fracture often occurs in the elastic region of the load-displacement curve as the load increases for notched high-strength steels charged with hydrogen. 16,17) In contrast, the results for the X80 specimens showed that they did not fracture suddenly but rather under plastic deformation as the load was increased as indicated in Figs. 5 and 6.…”
Section: Processes From Incubation Stage To Qc Crack Initiationmentioning
confidence: 86%
“…Thus, understanding the hydrogen (H) induced fracture mechanism(s) of these materials is challenging in spite of the availability of extensive literature on their susceptibility [1,[9][10][11][12][13][14]. In general, the susceptibility of a Q & T steel to HE could be related to the mechanical properties such as yield strength, toughness, hardness etc.…”
Section: Introductionmentioning
confidence: 99%